Tracking the Footprints of Spin Fluctuations: A MultiMethod, MultiMessenger Study of the Two-Dimensional Hubbard Model - Schaefer, Thomas; Wentzell, Nils; Simkovic, Fedor; He, Yuan-Yao; Hille, Cornelia; Klett, Marcel; Eckhardt, Christian J.; Arzhang, Behnam; Harkov, Viktor; Le Regent, Francois-Marie; Kirsch, Alfred; Wang, Yan; et al. (Physical Review X, 2021)
The Hubbard model represents the fundamental model for interacting quantum systems and electronic correlations. Using the two-dimensional half-filled Hubbard model at weak coupling as a testing ground, we perform a comparative study of a comprehensive set of state-of-the-art quantum many-body methods. Upon cooling into its insulating antiferromagnetic ground state, the model hosts a rich sequence of distinct physical regimes with crossovers between a high-temperature incoherent regime, an intermediate-temperature metallic regime, and a low-temperature insulating regime with a pseudogap created by antiferromagnetic fluctuations. We assess the ability of each method to properly address these physical regimes and crossovers through the computation of several observables probing both quasiparticle properties and magnetic correlations, with two numerically exact methods (diagrammatic and determinantal quantumMonte Carlo methods) serving as a benchmark. By combining computational results and analytical insights, we elucidate the nature and role of spin fluctuations in each of these regimes. Based on this analysis, we explain how quasiparticles can coexist with increasingly long-range antiferromagnetic correlations and why dynamical mean-field theory is found to provide a remarkably accurate approximation of local quantities in the metallic regime. We also critically discuss whether imaginary-time methods are able to capture the non-Fermi-liquid singularities of this fully nested system.
CRIS-Team WoS Importer:2021-04-02